Mesolithic harpoons from Odmut, Montenegro: Chronological, contextual, and techno-functional analyses. (22nd November 2016) - Cristiani, Emanuela; Borić, Dušan
Abstract: The (re-)appearance of harpoon technology during the Mesolithic in the southern Dinaric Alps is discussed by presenting the results of contextual, technological and use-wear analyses on the sample of 36 osseous harpoon specimens recovered in Mesolithic and Early Neolithic levels of the rockshelter of Odmut in western Montenegro. The assemblage of harpoons from this site is unique in Balkan prehistory, as there is currently limited evidence for the use of barbed weaponry prior to the regional Late Mesolithic. Technological and functional data related to the introduction of harpoon technology at Odmut and the southern Dinaric Alps are discussed against the background of the appearance of harpoons in the Alpine regions of Switzerland, Italy, and the northern Adriatic. Reasons and mechanisms that might have fostered the spread of harpoons in the circum-Adriatic region and a late use of harpoon technology in Montenegro are discussed.